Comparison of tracheal intubation conditions after 45 seconds, 60 seconds rocuronium and succinylcholine treatments in elective surgery - Muhdar Abubakar, Muhdar Abubakar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
The tracheal intubating conditions of rocuronium and succinylcholine under balanced anasthesik with midazolam, fentanyl, penthotal, nitrous oxide, oxigen and halothane were studied in 38 patients undergoing elective surgery. Patients were given either 0.6 mg/kg rocuronium or 1 mg/kg succinylcholine intravenously. forty five seconds after the administralon of rocuronium, or 60 seconds after the administration of rocuronium or succinylcholine, the trachea was intubated and the intubating conditions were scored by blinded assessor. Intubating conditions were the same between the rocuronium and succinylcholine group. (p = 0.18) The hemodynamic effect were the same among the three groups. The result showed that all patients with 0.6 mg/kg rocuronium could be Intubated within 45 seconds as well as 60 seconds; however, those intubated within 60 seconds were similar to those with 1 mg/kg sucdnylcholin.Key words: intubating conditions - rocuronium - succinylcholine - tracheal intubation - hemodynamic effect